SIMPATA: Integrasi Administrasi dan Monitoring Progres Kegiatan Magang Berbasis Web - Afif Rifai Nimal Abdu; Hanifah Permatasari; Agustina Srirahayu (Bulletin of Computer Science Research, 2026)
Internship management at the Statistics Indonesia Office of Sukoharjo Regency still relies on several separate and unintegrated media, covering document submission and verification, attendance recording, activity documentation, and participant task-progress monitoring. This condition causes data to be scattered, makes the recapitulation process less practical, and prevents participant activities from being monitored through a single system. This study aims to design and develop SIMPATA (Internship Participant Management and Governance Information System) as a web-based system that integrates internship administration and activity monitoring. The system was developed using an adapted Extreme Programming approach through the stages of planning, design, coding, and testing. Research data were collected through interviews, observations, and literature studies. The system was designed using the Unified Modeling Language, while its implementation employed PHP, the Laravel framework, and a MySQL database. The main contribution of SIMPATA lies in integrating registration, document verification, acceptance-status determination, participant and supervisor management, digital attendance, activity logbooks, task assignment, work submission, and progress monitoring into a single system. Black-box testing involving ten test scenarios showed that all major functions operated according to the specified functional requirements. Furthermore, User Acceptance Testing involving one administrator, three supervisors, and ten students obtained an overall score of 88.71%, which was classified in the Strongly Agree category. These results indicate that SIMPATA was well accepted by its users and can support more centralized and well-documented internship administration and activity monitoring.